Feasibility, acceptability, and preliminary efficacy of smartphone-based virtual reality relaxation in chemotherapy patients: A pilot study - Made Satya Nugraha Gautama; Haryani Haryani; Tsai Wei Huang; Ariani Arista Putri Pertiwi; Devi Rohmah Sholihatun; Uki Noviana (Tehran University of Medical Sciences, 2024)
Background & Aim: While virtual reality holds promise for enhancing patient management and experience during chemotherapy, its use remains limited. The present study aimed to test the feasibility, acceptability, and preliminary efficacy of smartphone-based virtual reality relaxation (SVR) in chemotherapy patients. Methods & Materials: In this pilot study, 29 participants were divided into two groups. The SVR group (n=14) experienced a 10-minute virtual reality intervention, while the control group (n=15) received standard care and guided imagery leaflets. Outcomes such as comfort, anxiety, pain, systolic blood pressure (SBP), diastolic blood pressure (DBP), and pulse rate were evaluated at baseline and post-chemotherapy. The Technology Acceptance Model (TAM) questionnaire and open-ended questions evaluated SVR's acceptability. Data was analyzed using descriptive statistics, non-parametric t-tests, and thematic analysis. Results: The SVR intervention appears feasible, as evidenced by a high recruitment rate of 93.75% (30 out of 32 eligible patients) and a retention rate of 96.67% (29 out of 30 participants), despite one withdrawal. The SVR group showed significant comfort improvement (P=0.002), significant changes in pulse rate (P=0.047), and SBP (P=0.023) compared to the control group. Anxiety, pain, pulse rate, and DBP showed no significant differences. A significant TAM variable (P<0.001) confirmed the intervention's acceptability. Qualitative feedback showed no serious side effects and patients reported positive experiences. Conclusion: The SVR intervention, feasible and acceptable, significantly improved comfort and altered pulse rate and SBP in chemotherapy patients. It shows potential as an oncology care strategy. Further validation is needed through large-scale trials.